A Multimodal Discourse Analysis of a McDonald’s Advertisement - Mudrikatun Ningamah; Lailatul Musyarofah; Endah Alamsari Andayani (Journal of English Language and Education, 2026)
This study aims to describe how McDonald’s advertisement constructs persuasive meaning and brand identity through multimodal discourse. The research employs a qualitative descriptive approach using multimodal discourse analysis based on the framework of Kress and van Leeuwen (2006). The data consist of selected McDonald’s advertisement materials containing both visual and linguistic elements. Data were collected through observation and documentation, then analyzed by identifying visual components such as color, typography, layout, and food imagery, as well as linguistic features including slogans and promotional texts. The analysis further examines the inters miotic relationship between visual and verbal modes to understand how they work together in creating meaning. The findings reveal that visual elements and linguistic messages are strategically integrated to attract attention, evoke positive emotions, and reinforce McDonald’s brand identity. Colors, imagery, and layout create visual appeal, while concise and persuasive language strengthens the promotional message. The study concludes that the advertisement’s effectiveness stems from the seamless interaction between different semiotic modes, producing a cohesive and emotionally engaging message. These findings demonstrate how global brands maintain market dominance through sophisticated multimodal communication strategies that resonate with the psychological needs and consumption patterns of modern consumers.